From capital surges to drought : - Ffrench-Davis, Ricardo (Palgrave Macmillan, 2003)
Senior bankers, regulators, and well-known academics explain the behavior of different players. The book breaks new ground by showing in detail how such behavior has contributed to the decline of flows and their volatility. The book suggests what coping mechanisms developing countries could adopt to deal with crisis situations; what measures should be taken at the national and international levels to make recipient countries less vulnerable to international financial instability; how such instability can be reduced; and what can be done on the source countries to encourage larger more stable capital flows to developing countries.